GREEN PACKAGING, GREEN PRODUCT, GREEN ADVERTISING, PERSEPSI, DAN MINAT BELI KONSUMEN - Santoso, Imam; Fitriani, Rengganis (Jurnal Ilmu Keluarga dan Konsumen, 2016)
Environmental problems become one of the strategic issues in achieving global competitiveness. One of the issues is products that are made from environmental friendly materials or known as green product. Furthermore, in green products marketing, the company also uses green packaging and green advertising concept. This study aimed to analyze the effect of green packaging, green products, and green advertising on consumer perception and purchasing intention. The study was conducted in Ketawanggede Village, Lowokwaru Sub-district, Malang City. The sampling method used nonprobability accidential sampling techniques. The numbers of respondents were 113 consumers in study site. Data were collected by interview using questionnaires. The method of analysis used Generalized Structured Component Analysis (GSCA). The analysis showed that the green packaging, green products, and green advertising had positive significant influence on consumer perceptions. Meanwhile, green product and consumer perception had positive significant influence on purchasing interest, but the green packaging and green advertising has not found sufficient evidence in influencing purchasing intention.